Galectin-1 Impairs the Generation of Anti-Parasitic Th1 Cell Responses in the Liver during Experimental Visceral Leishmaniasis - Bunn, Patrick T.; Montes de Oca, Marcela; Rivera, Fabian de Labastida; Kumar, Rajiv; Edwards, Chelsea L.; Faleiro, Rebecca J.; Ng, Susanna S.; Sheel, Meru; Wang, Yulin; Amante, Fiona H.; Haque, Ashraful; Engwerda, Christian R. (Frontiers in Immunology, 2017)
Many infectious diseases are characterised by the development of immunoregulatory pathways that contribute to pathogen persistence and associated disease symptoms. In diseases caused by intracellular parasites, such as visceral leishmaniasis (VL), various immune modulators have the capacity to negatively impact protective CD4+ T cell functions. Galectin-1 is widely expressed on immune cells and has previously been shown to suppress inflammatory responses and promote the development of CD4+ T cells with immunoregulatory characteristics. Here, we investigated the role of galectin-1 in experimental VL caused by infection of C57BL/6 mice with Leishmania donovani. Mice lacking galectin-1 expression exhibited enhanced tissue-specific control of parasite growth in the liver, associated with an augmented Th1 cell response. However, unlike reports in other experimental models, we found little role for galectin-1 in the generation of IL-10-producing Th1 (Tr1) cells, and instead report that galectin-1 suppressed hepatic Th1 cell development. Furthermore, we found relatively early effects of galectin-1 deficiency on parasite growth, suggesting involvement of innate immune cells. However, experiments investigating the impact of galectin-1 deficiency on dendritic cells indicated that they were not responsible for the phenotypes observed in galectin-1-deficient mice. Instead, studies examining galectin-1 expression by CD4+ T cells supported a T cell intrinsic role for galectin-1 in the suppression of hepatic Th1 cell development during experimental VL. Together, our findings provide new information on the roles of galectin-1 during parasitic infection, and indicate an important role for this molecule in tissue-specific Th1 cell development, but not CD4+ T cell IL-10 production.